2015
DOI: 10.2147/ijnrd.s84061
|View full text |Cite
|
Sign up to set email alerts
|

IgA-dominant post-infectious glomerulonephritis presenting as a fatal pulmonary-renal syndrome

Abstract: Over the last decades, post-infectious glomerulonephritis underwent major changes in its epidemiology, pathophysiology, and outcomes. We are reporting a case of IgA-dominant post-infectious glomerulonephritis (IgA-PIGN) presenting as a fatal pulmonary-renal syndrome. An 86-year-old Filipino man presented with worsening dyspnea, hemoptysis, and decreased urine output over 2 weeks. Past medical history is significant for hypertension, chronic kidney disease stage III, and pneumonia 3 weeks prior treated with int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Its pathogenesis was similar to that of active IgA nephropathy, and the clinical and pathological manifestations were highly similar. Marc Saad et al [ 8 ]also reported a case with pulmonary-renal syndrome as the main manifestation. The above study found some difficulty in differentiating IgA-dominant postinfectious glomerulonephritis when the presentation is atypical from other glomerulonephritis, especially primary IgA nephropathy, which can have similar light microscopy and immunofluorescence manifestations, but the treatment options for the two are different, and the prognosis of patients with IgA-dominant postinfectious glomerulonephritis is often reported worse [ 15 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Its pathogenesis was similar to that of active IgA nephropathy, and the clinical and pathological manifestations were highly similar. Marc Saad et al [ 8 ]also reported a case with pulmonary-renal syndrome as the main manifestation. The above study found some difficulty in differentiating IgA-dominant postinfectious glomerulonephritis when the presentation is atypical from other glomerulonephritis, especially primary IgA nephropathy, which can have similar light microscopy and immunofluorescence manifestations, but the treatment options for the two are different, and the prognosis of patients with IgA-dominant postinfectious glomerulonephritis is often reported worse [ 15 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Five IgA-mediated syndromes presenting with PRS need to be distinguished from IgAN-related DAH. These include HSP, 58 IgAN-ANCA vasculitis overlap syndrome, IgA-dominant post-infectious glomerulonephritis (IgA-PIGN) 63,64 IgA-variant Goodpasture's syndrome [53][54][55][56][57] and IgA-producing monoclonal gammopathy. 52 HSP is characterized by a tetrad of cutaneous purpura, arthritis, abdominal pain and nephritis.…”
Section: Discussionmentioning
confidence: 99%
“…66 IgA-PIGN is a recently described entity that can present with pulmonary edema or DAH. 63,64 The older age, prevalence of diabetes, preceding staphylococcal infection as a trigger, low complement levels, acute renal failure at presentation with diffuse proliferative glomerulonephritis and diffuse C3 > IgA on IIF, j > k light chains and subepithelial deposits on IIF help distinguish these entities. 63,69 IgA-variant GPS is defined by the linear pattern on IIF staining of the kidneys and presence of a monoclonal IgA-j circulating antibody.…”
Section: Discussionmentioning
confidence: 99%
“…In 27 (60%) cases, both chains were deposited equally; however, in 16 (35.5%) cases, lambda light chain staining was dominant. EM study showed that sub-epithelial, sub-endothelial, and mesangial areas were the most common sites of Ig deposition (29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42).…”
Section: Pathology Of Iga-pignmentioning
confidence: 99%